(untitled) (Bangladesh Journal of Medicine, 2023)
Background: The treatment of cerebral palsy is multifactorial. The aim of the study is to find out the efficacy of tizanidine and intensive rehabilitation in the treatment of spastic cerebral palsy. Methods: This observational study was conducted over 35 patients in Sir Salimullah Medical Mitford Hospital from January 2022 to December 2022.The patients satisfying the inclusion and exclusion criteria were enrolled: total 35 patients received tizanidine (2mg) orally at a dose of 1 mg given at bed time under 10 years and 2 mg given at bed time more than 10 years of age, then after 1 week maintenance dose was given at 0.3 mg/kg/day, three times daily in combination with intensive rehabilitation 1 hour daily five times a week. Total 24 weeks of intensive rehabilitation was given. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks. Results: The study shows high efficacy in reducing tone in spastic cerebral palsy measured by using Modified Ashworth scale (p<0.001).Also there is improvement in physician rating scale crouch (p<0.0001) and foot contact, (p<0.0001) and also improvement in gross motor function (p<0.01). Conclusion: Combination of tizanidine and intensive rehabilitation is effective for reduction of generalized spasticity regarding muscle tone, range of motion of the joint and improvement of gait in cerebral palsy patients. Bangladesh J Medicine 2023; 34(3): 223-228